2012
DOI: 10.1371/journal.pone.0037336
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Cesarean Delivery on Maternal Request and Method of Newborn Feeding in China

Abstract: BackgroundCesarean delivery has increased significantly during the last decades. This study aimed to investigate the association between planned mode of delivery and method of feeding.Methodology/Principal FindingsA cohort was created retrospectively using data from a population-based maternal and child health surveillance system, which covers 27 study sites in China from 1993 to 2006. The cohort consisted of 431,704 women for analysis, including 22,462 women with planned cesarean delivery on maternal request … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
22
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 19 publications
7
22
0
Order By: Relevance
“…Traffic-related air pollution has been found to be associated with the development of asthma and allergies during the first 8 years of life [52,56]. Another possible contributory factor is the increased percentage of births by Cesarean delivery in China [57], which may be associated with increased risk of asthma and allergy rates [58].…”
Section: Prevalence Of Childhood Asthma In Beijingmentioning
confidence: 99%
“…Traffic-related air pollution has been found to be associated with the development of asthma and allergies during the first 8 years of life [52,56]. Another possible contributory factor is the increased percentage of births by Cesarean delivery in China [57], which may be associated with increased risk of asthma and allergy rates [58].…”
Section: Prevalence Of Childhood Asthma In Beijingmentioning
confidence: 99%
“…Maternal issues include mother's age, marital status, occupation, parity, educational level, social and/or health status, multiple pregnancy, mode of delivery, perception of insufficient milk supply (6)(7)(8)(9)(10)(13)(14)(15), and problems related to the feeding process, for example inefficient 'latch', nipple pain etc. (13).…”
Section: Resultsmentioning
confidence: 99%
“…Some observational studies dealing with maternal factors affecting initiation and continuation of breast feeding revealed that mother's age, education or parity did not affect the rate of breast feeding (10), while others noticed that older age, higher maternal education and multi-parity were associated with higher likelihood of breast feeding at 6 months of age (6)(7)(8). On the other hand, maternal employment, cesarean delivery and infant hospitalization are recognized risk factors for early discontinuation of EBF (10,14,15,25).…”
Section: Resultsmentioning
confidence: 99%
“…The average gestational age is significantly lower in the group of cesarean delivery with no indication as compared to the planned vaginal delivery group in four of the five studies evaluating this outcome (Table 4) (B). [3][4][5][6]9 The mean birth weight is assessed in five studies, and in one work, only the mean weight is significantly higher in the cesarean group without indication (Table 5) (B). [3][4][5][6]8 Effect of cesarean section on maternal request or without indication on maternal mortality Three studies evaluate maternal mortality (B); 2-4 however, only one study has events for this outcome (B).…”
Section: -10mentioning
confidence: 99%
“…The studies (B) 5,9 assessed the association between cesarean section on maternal request or without indication and complications in breastfeeding. The simple average of all the studies revealed that the rate of breastfeeding complications in the group of cesarean delivery on maternal request is 8.4 versus 7.4% in the group of planned vaginal delivery.…”
Section: Effect Of Cesarean Section On Maternal Request or Without Inmentioning
confidence: 99%